2017
DOI: 10.1097/bot.0000000000000862
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Liposomal Bupivacaine Administered With Standard Bupivacaine in Ankle Fractures Requiring Open Reduction Internal Fixation: A Single-Blinded Randomized Controlled Trial

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…The highest Cmax was observed in an individual taking the second dose 24 h after the first, but was below toxic levels for central nervous system and cardiac. In general, LB was well tolerated and revealed no clinically relevant unsafety signs (Rice et al 2017), provided excellent pain scores, lower opioids consumption, and at a lower cost (Mazloomdoost et al 2017;Sabesan et al 2017;Mcgraw-tatum et al 2017;Davidovitch et al 2017;Johnson et al 2017;Barron et al 2016). Thus, liposome formulation of the anesthetic rendered longer therapeutic times with no adverse effects.…”
Section: Pain Management: Bupivacainementioning
confidence: 87%
See 2 more Smart Citations
“…The highest Cmax was observed in an individual taking the second dose 24 h after the first, but was below toxic levels for central nervous system and cardiac. In general, LB was well tolerated and revealed no clinically relevant unsafety signs (Rice et al 2017), provided excellent pain scores, lower opioids consumption, and at a lower cost (Mazloomdoost et al 2017;Sabesan et al 2017;Mcgraw-tatum et al 2017;Davidovitch et al 2017;Johnson et al 2017;Barron et al 2016). Thus, liposome formulation of the anesthetic rendered longer therapeutic times with no adverse effects.…”
Section: Pain Management: Bupivacainementioning
confidence: 87%
“…A slow-release mechanism involving reorganization of the barrier lipid membranes is sustained for up to 92 h with concomitant pain control for up to 72 h, as compared to 7-12 h with standard bupivacaine. Studies show bupivacaine decreased pain compared to placebo, the use of opioids and the hospital costs (Yeung et al 2018;Mazloomdoost et al 2017;Sabesan et al 2017;Declaire et al 2017;Smith et al 2017;Mcgraw-tatum et al 2017;Abildgaard et al 2017;Alijanipour et al 2016;Davidovitch et al 2017). Although the liposomal bupivacaine is not a nanoparticle (3-30 μm mean diameter), it is mentioned here because it is one of the most recent liposomal formulations approved.…”
Section: Pain Management: Bupivacainementioning
confidence: 99%
See 1 more Smart Citation
“…32 In the trauma cohort, liposomal bupivacaine has been effective in lowering pain scores and decreasing narcotic use in patients undergoing ankle and distal radius surgeries. 33,34 The utility of liposomal bupivacaine in the geriatric hip fracture cohort has had limited investigation. Basmajian et al 35 studied liposomal bupivacaine versus a standardized oral pain control regimen in geriatric extracapsular hip fracture patients.…”
mentioning
confidence: 99%
“…10 Liposomal bupivacaine is a 72-hour slow-release anesthetic used frequently for orthopaedic and plastic surgery procedures and is associated with a reduced hospital length of stay (LOS). [12][13][14][15] Studies have shown the beneficial effects of liposomal bupivacaine for intercostal blocks during video-assisted thoracoscopic procedures, yet no study has evaluated this medication for intercostal nerve blocks in the treatment of traumatic rib fractures. 12 This study seeks to compare outcomes of epidural analgesia with intercostal nerve block using liposomal bupivacaine for the treatment of traumatic rib fractures.…”
mentioning
confidence: 99%